Umrah Sebagai Gaya Hidup, Eksistensi Diri dan Komoditas Industri: Menyaksikan Perubahan Keagamaan Warga Kota - Sucipto, Mr (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2013)
This paper explores the change in âthe meaningâ of umrah. Institutional constraints are explored as well as theoretical developments of umrah. These are discussed in the different levels such how middle class taking decisions about umrah, the meaning of umrah religiously and socially in perspective of experts, and the distance betweeen umrah as a religious effort and its developing specific intention. The last level of this article considering umrah motivation as âconstructions and selections from available knowledge which was crystallised as conventions and power-knowledge relations of religioâ. Personal reflections connected to theoretical considerations develop following particular project which entailed practicing umrah as an act of religion in leisure studies. It becomes possible to consider new directions for Leisure Studies as a part of religious research. Keywords: Umrah, komodifikasi, keagamaan.